Człowiek a Bóg w dramatach Amelii Hertzówny - Nazarewicz, Aneta Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2019)
Amelia Hertz still is an unfamiliar play wright. Recently the papers on her works are being released more often. Researchers do not take an interest in the relation of man towards God, though. This relationis a crucial element of her dramas. The importance of this theme is presented by the very structure of respective works. “Zburzenie Tyru” is a staging of biblical events. “Yseult o Białych Dłoniach” is structured like a confession. The events of “Wielki król” are motivated by a constantfear of the Wrath of God, who will inflict justice upon Byzantium. The ultimate defeat of the heroes is summarised with the words “Because only God is eternal”. The main characters of the dramas in their relation towards God correspond to the Kierkegaard’s typology: the aesthetical man, the ethical man and the religious man. Hertz uses Kierkegaard’s philosophy Either/Or, showing different variants of the same story and whatare the consequences of making decisions.
Keywords: Amelia Hertz; God; Søren Kierkegaard; drama